Adaptasi dan Validasi Instrumen The Perceived Wellness Survey (PWS) pada Peserta Didik SMA di Indonesia - Yuningsih, Ayu Tri; Herdi, Herdi (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
The Perceived Wellness Survey (PWS) is a multidimensional measure of perceived wellness perception in the psychological, emotional, social, physical, spiritual, and intellectual. This study aims to adapt and validate The Perceived Wellness Survey (PWS) instrument. The research sample used 123 high school students in Indonesia who were selected by convenience sampling technique. Operationally, data were analyzed using Confirmatory Factor Analysis (CFA) with LISREL version 8.80. The results showed that all indicators of goodness of fit (GOF) were not fit, where obtained were chi-square (1212.70), GFI (0.59), AGFI (0.53), RMSEA (0.11), and RMR (0.31).